Fuzzy control of milling chatter with piezoelectric actuators embedded to the tool holder. (1st February 2021) - Li, Denghui; Cao, Hongrui; Chen, Xuefeng
Highlights: A sensitive active chatter control structure with piezoelectric actuators is developed. Comb filters and fuzzy controllers are designed for targeted control of chatter components. The required control voltage of the actuator is significantly reduced. The proposed active chatter control method is experimentally verified. Abstract: Chatter is a typical kind of self-excited vibration occurred in the machining process. It not only results in inferior workpiece, but also shorts the life of the tool. It has become one of the main problems limiting machining efficiency. In order to suppress milling chatter, a novel active control method based on piezoelectric actuators embedded to the tool holder is proposed in this work. First of all, an active control structure is built by integrating piezoelectric actuators and displacement sensors into the tool holder, and the corresponding control system model is also developed. Then, a fuzzy controller is designed based on the dynamic characteristics of the spindle-tool holder-tool system. In the control process, the vibration displacements of the tool holder are measured and then fed back to the fuzzy controller after comb filtering of spindle rotation frequency and its harmonic components. Thus, the targeted control of chatter components is achieved. Next, a numerical simulation is performed on the basis of identified model parameters of the spindle-tool holder-tool system. Finally, the proposed method is experimentally verified through different milling tests. The results show that not only the chatter is effectively suppressed, but also the control energy of the actuators is significantly reduced.